(SCAFFOLDING BASED ON THE LEVEL OF SOLO TAXONOMY OF STUDENT’S MA BAHRUL ULUM JOMBANG IN SOLVING THREE DIMENSIONAL DISTANCE PROBLEMS) - Umardiyah, Fitri; Satiti, Wisnu Siwi; Nasrulloh, M. Farid (Prodi Pendidikan Matematika Universitas Pesantren Tinggi Darul Ulum Jombang, 2024)
Each student has a different level of ability to solve questions. These level differences indicate the need to provide scaffolding for students who experience difficulties. This research aims to describe the provision of scaffolding to students in the unistructural category in the SOLO Taxonomy level. The research subjects consisted of six students of class XII who were selected through the unistructural level SOLO Taxonomy classification test. This research is descriptive qualitative research. The instruments used are tests, interview guidelines and scaffolding guidelines. Scaffolding is given to students by referring to test and interview results. Scaffolding is provided so that students in the unistructural category can use more than one information/concept and link each concept together to be able to make relevant conclusions. The scaffolding used is level 2 scaffolding, namely explaining, reviewing restructuring, and level 3 scaffolding, namely developing conceptual thinking.